DEVELOPMENT OF ISLAMIC RELIGIOUS EDUCATION CURRICULUM AND ITS IMPLEMENTATION IN LEARNING IN PANDEMIC TIMES (Case study at Ad-Damanhuri Junior High School Bangkalan Madura) - Faisol Mubarok; Ilzam (Sean Institute, 2022)
This study describes the implementation of Islamic religious education curriculum development in PAI subjects with Fiqh material at Ad-Damanhuri Middle School during a pandemic. The method chosen in this study is a qualitative method. The data of this study were obtained from the results of recording by the teacher's notes. The data analysis technique used in this research is to classify, combine, interpret and conclude. The results of this study are curriculum development has the principles of relevance, continuity, practicality and effectiveness. The implementation of the curriculum at Ad-Damanhuri Middle School during this pandemic uses the national curriculum by taking into account various aspects.